Maternal vitamin D levels in hypertensive disorders of pregnancy - Tyagi, Vatika; Tyagi, Mamta; Gupta, Smriti; Khanuja, Esha; Varma, Yamini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Current study was conducted with the objective to evaluate maternal vitamin D levels in patients with hypertensive disorders of pregnancy. Methods: The present prospective observational study was conducted among 200 pregnant women attending gynaecological OPD of Subharti medical college, Meerut, over a period of two years and satisfying the inclusion criteria were enrolled. On admission, patient demographic profile, complete history was recorded, and comprehensive clinical examination was done. In all the patients, blood samples for routine examination along with LFT, RFT, random blood sugar, serum electrolytes, serum uric acid and serum vitamin D were drawn, and serum levels of these biochemical parameters were determined according to standard laboratory procedures. Subjects were classified into three categories according to serum vitamin D level i.e. >20 ng/ml (mild), 10-20 ng/ml (moderate deficiency), <10 ng/ml (severe deficiency). Results: Insignificant difference was found between case (hypertensive) and control (normotensive) group when compared in relation to age, education, parity and socioeconomic status. The mean vitamin D level of women with HDP was 5.7+2.99 ng/ml as compared to 17.34+5.79 ng/ml in normotensive women with statistically significant difference as p<0.001. No correlation was found between severity of vitamin D deficiency and maternal complications (p=0.318). Conclusions: The results of the present study concluded that women with hypertension had significantly lower vitamin D level as compared to normotensive women.